2020
DOI: 10.3390/cells9091946
|View full text |Cite
|
Sign up to set email alerts
|

Glycan Node Analysis of Plasma-Derived Extracellular Vesicles

Abstract: Blood plasma is a readily accessible source of extracellular vesicles (EVs), i.e., cell-secreted nanosized carriers that contain various biomolecules, including glycans. Previous studies have demonstrated that glycans play a major role in physiological and pathological processes, and certain plasma glycans have been associated with disease conditions. However, glycome studies have been limited by a lack of analytical techniques with the throughput capacity necessary to study hundreds of clinical samples. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Nevertheless, the N -glycome of exosomes from hepatocellular carcinoma patient samples was characterized using a reverse capture strategy, and the majority of the N -glycans found in EVs from patients with HCC were modified with sialic acids or fucoses, in contrast to the N -glycans identified in EV from healthy samples [ 151 ]. Walker et al also reported significant differences between the glycan profiles identified directly in the plasma or the plasma-derived EVs from the same individuals [ 217 ]. Interestingly, a new integrated analytical platform, termed the integrated magnetic analysis of glycans in extracellular vesicles (iMAGE), was developed to directly analyze the EV glycosylation profile in biological samples.…”
Section: Cancer Extracellular Vesicles Glycosylationmentioning
confidence: 99%
“…Nevertheless, the N -glycome of exosomes from hepatocellular carcinoma patient samples was characterized using a reverse capture strategy, and the majority of the N -glycans found in EVs from patients with HCC were modified with sialic acids or fucoses, in contrast to the N -glycans identified in EV from healthy samples [ 151 ]. Walker et al also reported significant differences between the glycan profiles identified directly in the plasma or the plasma-derived EVs from the same individuals [ 217 ]. Interestingly, a new integrated analytical platform, termed the integrated magnetic analysis of glycans in extracellular vesicles (iMAGE), was developed to directly analyze the EV glycosylation profile in biological samples.…”
Section: Cancer Extracellular Vesicles Glycosylationmentioning
confidence: 99%
“…Native LDL was desialylated with neuraminidase enzyme and added to the LAK cells at day 5 at 50 μg/ml and incubated for 72 hours. Our glycan node analysis procedure [33][34][35][36][37][38] was used to verify LDL desialylation prior to adding the LDL samples to the LAK cells. An increase in the relative abundance of terminal galactose, a decrease in 3-linked galactose, and a near-complete loss of 6-linked galactose revealed a major decrease in the number of terminal sialic acid residues present on LDL (Supplementary Fig.…”
Section: Oxidized-desialylated Ldl Inhibits Lak Cell Cytotoxicity In Vitromentioning
confidence: 99%
“…Samples were reconstituted in 450 μl of 10 mM HEPES in 0.15 M NaCl pH 7 buffer each time for a total of 4 spin throughs. To verify complete desialylation of LDL, the glycan node analysis method [33][34][35][36][37][38] was used. Glycan node analysis is a procedure based on glycan methylation analysis by which pooled glycans within whole biological samples are deconstructed in a way that conserves their monosaccharide and linkage information [33].…”
Section: Desialylation Of Low-density Lipoprotein and Glycan Node Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, extracellular vesicles (EVs) have generated considerable interest due to their involvement in physiological and pathological intercellular communication [ 1 , 2 , 3 , 4 ]. EVs are composed of an external bilayer formed by lipids [ 5 ], proteins [ 6 ], and glycans [ 7 ] that enclose an aqueous core with additional bimolecular cargo, such as nucleic acids [ 8 ]. EVs are released by all cells and are classified based on biogenesis, but subtypes also differ in terms of size and composition.…”
Section: Introductionmentioning
confidence: 99%